Enhancing teaching in higher education : new approaches for improving student learning - Hartley, Peter; Woods, Amanda; Pill, Martin (Routledge, 2005)
This book brings together a collection of ground-breaking research and tested techniques in the field of learning and teaching in higher education. It provides an accessible, authoritative account of the latest developments, outlining how to apply learning theory and best practice to everyday teaching and providing advice on overcoming problems of implementation. Evidence is drawn from funded projects and innovative practitioners from a wide range of disciplines and backgrounds and covers areas including approaches to learning, working with students, enhancing the progress and
Keywords: College teaching; Learning